PENGEMBANGAN EKOWISATA DI KAWASAN WADUK KEULILING KECAMATAN KUTA COT GLIE KABUPATEN ACEH BESAR - Maulidan Mahmud; Ashfa Achmad; Azmeri Azmeri (Prodi Magister Teknik Sipil Unsyiah, 2020)
The management of the Keuliling Reservoir area as a tourist attraction is still lacking the attention of the government so that it affects the decline in the quality of reservoir facilities and infrastructures such as parking areas, mushallas, bathrooms, gazebos, view towers, and children's pools. This study aims to model the factors of ecotourism development in reservoir areas against local economic growth, and to find ecotourism development strategies in reservoir areas. This research uses qualitative methods through observation and interviews, and quantitative methods through distributing questionnaires. Respondents in this study aimed at residents of Bak Sukon Village, with a total sample of 87 people. The statistical method used is descriptive analysis and multiple linear regression analysis using statistical software. The formulation of an ecotourism development strategy is carried out through a Focus Group Discussion (FGD), which consists of ten academics, community leaders, the private sector, and the community. The results showed that the model of ecotourism development factors in the Keuliling Reservoir area that influenced local economic growth in Bak Sukon Village were explanatory factors, improved facilities, ecotourism attractions, ecotourism access, ecotourism facilities, and service factors, with a regression model Y = 0.187X1 + 0,223X2 + 0,303X3 + 0,310X4 + 0,182X5 + 0,173X6. The strategy for developing ecotourism in the Keuliling Reservoir area is zoning, making local government policies, establishing an ecotourism management body, implementing ecotourism development, engaging community participation, and evaluating ecotourism area management activities.